Shaun the sheep. The flight before Christmas [videorecording (DVD)] - Pilbrow, Giles; Burton, Mark, 1960- (Shaun the sheep., 2023)
It's Christmas Eve at Mossy Bottom Farm and Shaun's seasonal excitement turns to dismay when a farmhouse raid to get bigger stockings inadvertently leads to Timmy getting lost in the local Christmas market. Shaun's rescue mission to town goes wrong when a gift box containing Timmy disappears off in a 4x4 driven by Farmer Ben, a local celebrity and influencer. Can Shaun save the day and get Timmy home in time for Christmas? Or has Shaun finally met his match in Farmer Ben's feisty daughter, Ella? Prepare for an explosive high-wire ending as everyone learns the true value of Christmas!